2011
DOI: 10.1007/s00240-011-0392-8
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic diagnosis in stone formers in relation to body mass index

Abstract: It is known that several metabolic abnormalities that favor stone formation have a strong dependence on environmental and nutritional factors. The incidence and prevalence of kidney stone is increasing while there has been a parallel growth in the overweight/obesity rate, and epidemiologic studies have shown a significant association between overweight/obesity and increased nephrolithiasis risk. The aim of this study was to assess if metabolic abnormalities observed in stone patients differ in relation to thei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
9
0
1

Year Published

2012
2012
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 20 publications
2
9
0
1
Order By: Relevance
“…Del Vella and colleagues found significantly higher obesity rates in men than in women with urolithiasis. 17 Similar conclusions were found by Daudonet and colleauges. 18 As a result, higher BMI in men means that an increased incidence of kidney stones will also increase in men.…”
Section: Discussionsupporting
confidence: 80%
“…Del Vella and colleagues found significantly higher obesity rates in men than in women with urolithiasis. 17 Similar conclusions were found by Daudonet and colleauges. 18 As a result, higher BMI in men means that an increased incidence of kidney stones will also increase in men.…”
Section: Discussionsupporting
confidence: 80%
“…41 Not surprisingly, the mean scores of BMI were above 25 and therefore can be classified as overweight or obese grade I. 4,42 Spinal manipulation increased trunk flexion at T12-L1 levels in the EG. The mechanical force introduced into the spine during SMT may alter the segmental biomechanics through the release of adhesions, the trapped meniscus or reducing the distortion of the annulus fibrosus.…”
Section: Discussionmentioning
confidence: 96%
“…Recurrence rates of 50% after 10 years and 75% after 20 years have been reported. 2 The etiological factors of kidney stone formation are complex and diverse and involve genetic, metabolic and environmental risk factors, 3 some of which may be adjustable; 4,5 so that the stone formation usually results from an imbalance between factors that promote urinary crystallization, and those that inhibit crystal formation and growth. 6 The most important data appear to be related to the links between genetic variability and urine calcium excretion and pH, so these risk factors seem to be at the very center of the problem of kidney stone disease.…”
mentioning
confidence: 99%
“…Using a BMI cutoff of 30, the RRs were 1.33, 1.90, and 2.09, respectively. Similarly, in a study of more than 800 renal stone formers, Del Valle and colleagues 41 showed that most patients (nearly 60%) were either overweight or obese. In 2006, Taylor and Curhan 42 investigated the relationship of BMI as a continuous variable to stone formation, and noted that even in nonobese patients (BMI <30), an increasing BMI lent itself to a higher risk of urolithiasis.…”
Section: Obesity Diabetes and Urinary Stone Diseasementioning
confidence: 89%